The Effectiveness of Event Promotion by Using Social Networking Site (SNS) - Mazdan, Ali Amaran; Sabirah, Sulaiman; Alexander, Chelum; Mawar Suhaila, Ab Razak (Secholian Publication (Kuala Lumpur, Malaysia), 2023)
The evolution of the era showed people had changed their living style. To conduct their regular chores, people today need technological gadgets like tablets, smartphones, and PCs. While the majority of individuals now consider having access to the Internet and different social media platforms to be a norm and part of their everyday lives. It indicates the importance of the Internet and social media in people's daily lives nowadays and the widespread use of social media as a promotional tool by the majority of businesses. However, is there effective in promoting the events and reliable to promote the event? In order to determine the efficiency of event advertising, this study will look at the Social Networking Site (SNS) channel.This study involved 200 surveys among event participants using simple random sampling in Kuching City, Sarawak. The results of the descriptive study indicate that the SNS channels are the factors that can affect how well an event is promoted.